EVALUATING THE PERFORMANCE OF SEVERAL ALGORITHMS USING WEKA IN RED WINE QUALITY - Dellosa, Rhowel M (Journal of Agriculture and Technology Management; Vol 26 No 1 (2023): Vol 26 No 1 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 January - June 2023 Issue, 2023)
The study aimed to evaluate the performance of various regression algorithms performed at predicted values. WEKA program and a dataset from a reputable source were utilized. The study was initiated to compare the performance of several regression algorithms. The result shows that the KStar (r = 0.6043) has the highest correlation coefficient, followed by Gaussian Processes (r = 0.5908) and followed by M5Rules (r= 0.5904). It also shows that the Linear Regression (r =0.5872) has good results as well as the SMOreg (r = 0.5623). All of the 11 functions, rules and lazy algorithms have moderate performance except for the ZeroR which resulted in a negative correlation. Future work may consider the use of WEKA in other similar prediction analyses.